Analysis of income and added value of oil palm and sugar palm diversification in Bandar Sei Kijang District, Pelalawan Regency - Yeni Kusumawaty; Evy Maharani; Rindi Tiara; Susy Edwina; Sispa Pebrian (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2025)
The fluctuating price of oil palm affects farmers' income, so that farmers carry out monoculture sugar palm farming and diversification with oil palm. This study aimed to analyze income, efficiency and added value of oil palm and sugar palm diversification and analyze income and efficiency of monoculture sugar palm farming in Bandar Sei Kijang District, Pelalawan Regency. The research applied a survey method. The results of the study showed that the income of oil palm farming is IDR 1,015,441.51/ha/month, income of sugar palm farming is IDR 2,658,468.89/month, income of sugar palm sap coffee business is IDR 5,646,855.65/month and income of sugar palm sap tea is IDR 139,019.83/month. Palm oil, sap coffee and tea, and sugar palm sap businesses are categorized as efficient and profitable and worth continuing because the R/C value is 1. The added value of sap coffee and sap tea products is relatively high because the added value ratio is more than fifty percent. The income from monoculture sugar palm farming is IDR 375,081.83/month, monoculture sugar palm farming is categorized as efficient and profitable and worthy of being continued.